2017
DOI: 10.1007/s11908-017-0598-1
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Aortic Graft Infection in the Endovascular Era

Abstract: Definitive therapy for aortic graft infection continues to include parenteral antibiotics and surgical explantation and revascularization procedures, which are historically vast operations and sources of significant operative stress. Surgical management has evolved to include more options for infection resistant in situ conduits, attempts at partial explantations, and use of endovascular therapy to temporize the urgent sequelae of these infections, such as aortoenteric fistula. Aortic graft infection continues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…6,11 Symptoms of stent graft infection and AEF include chronic fever, abdominal pain, leukocytosis, bacteremia, weight loss, weakness, and bleeding, but reportedly 10% of patients remain asymptomatic. 3,6,12 Chaufour et al reported a median time from initial EVAR and first signs of infection of 414 days (range up to 9 years) and a median time to endograft explantation of 30 days (range up to 2.2 years). 2 In addition to CT scans, FDG-PET scans and leukocyte scintigraphy show higher sensitivity and may provide further information to assess the extent and origin of a suspected inflammatory process.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…6,11 Symptoms of stent graft infection and AEF include chronic fever, abdominal pain, leukocytosis, bacteremia, weight loss, weakness, and bleeding, but reportedly 10% of patients remain asymptomatic. 3,6,12 Chaufour et al reported a median time from initial EVAR and first signs of infection of 414 days (range up to 9 years) and a median time to endograft explantation of 30 days (range up to 2.2 years). 2 In addition to CT scans, FDG-PET scans and leukocyte scintigraphy show higher sensitivity and may provide further information to assess the extent and origin of a suspected inflammatory process.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] A prophylactic systematic antibiotic therapy prior to any procedure or illness (ie, urinary tract infection, pneumonia, and dental treatment) following EVAR has been recommended to avoid potential endograft contamination. 2,5 An in situ reconstruction, with previous complete endograft removal and removal of necrotic tissue, provides an alternative approach, avoiding most of the risks of extra-anatomic technique 6,12,13 but still facing high risk of reinfection. Autologous veins and cryopreserved allografts bear a risk of rupture, aneurysm formation, thrombosis, and occlusion but are considered favorable over prosthetic grafts (eg, rifampicin-soaked Dacron) that are associated with reinfection rates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 However, the presence of an aortoenteric fistula (AEF), a poor prognosticator, concurrent with a fenestrated aortic endograft explantation may further increase perioperative mortality to prohibitive levels. 4…”
Section: Introductionmentioning
confidence: 99%